Determinants of local government capital expenditure in Indonesia: Fiscal capacity, local revenue, and BPK’s audit opinion - Marwatul Hasanah; Andi Chairil Furqan; Muliati Muliati; Erwinsyah Erwinsyah (Institute of Accounting Research and Novation (IARN), 2026)
Differences in fiscal capacity, local revenue, and financial accountability may contribute to variations in capital expenditure allocation among Indonesian local governments. Understanding these factors is important because capital expenditure supports public infrastructure provision and long-term regional development. This study examines the effects of the Fiscal Capacity Index (FCI), Local Own-Source Revenue (LOSR), and BPK audit opinion on capital expenditure. A quantitative explanatory approach was employed using secondary data obtained from the Ministry of Finance of the Republic of Indonesia and BPK audit reports. The sample comprises 542 local governments observed from 2021 to 2023, resulting in 1,626 panel observations. Panel data regression analysis was used to estimate the relationships between the explanatory variables and capital expenditure. The findings indicate that the Fiscal Capacity Index has a positive and significant effect on capital expenditure. Local Own-Source Revenue also has a positive and significant effect and exhibits the largest coefficient, suggesting that fiscal autonomy plays the strongest role in explaining capital expenditure allocation. In contrast, BPK audit opinion has a negative but statistically insignificant effect on capital expenditure. Overall, fiscal capacity and local revenue are significant determinants of capital expenditure allocation, whereas BPK audit opinion is not significantly associated with capital expenditure among Indonesian local governments.